Safety, Virology and Pharmacokinetics of Oseltamivir in Infants with Laboratory-Confirmed Influenza: A Phase I/II, Prospective, Open-Label, Multicentre Clinical Trial. Issue 8 (November 2015) - Rath, Barbara A; Brzostek, Jerzy; Guillén, Sara; Niranjan, Vis; Chappey, Colombe; Rayner, Craig R; Clinch, Barry
Background: The influenza antiviral oseltamivir is not licensed for infants aged <1 year in most countries outside the United States. More information is needed on oseltamivir safety at different dosing levels in this vulnerable age group. Methods: In this prospective, observational, non-randomized study, infants aged <1 year with laboratory-confirmed influenza were treated with oral oseltamivir for 5 days. Cohorts 1, 2 and 3 (aged 91–364, 31–90 and 0–30 days, respectively), received twice-daily dosages of 3, 2.5 and 2 mg/kg, respectively. Assessments included pharmacokinetics, on-treatment adverse events, resistance testing and viral shedding. Results: A total of 65 patients were enrolled: 40, 20 and 5 in cohorts 1, 2 and 3, respectively. Systemic exposure to oseltamivir carboxylate (active metabolite) reached therapeutic levels in all patients, with an adequate safety margin. On-treatment adverse events ( n =48) were reported by 32 patients (49%). At least one adverse event was reported by 43%, 65% and 40% of infants in cohorts 1, 2 and 3, respectively; most frequently vomiting and diarrhoea. Eight serious adverse events were reported, all of which were considered unrelated to treatment by the investigator. No deaths occurred and no patient had treatment withdrawn. Oseltamivir resistance mutations were detected in eight patients. Conclusions: Oseltamivir dosages of 2–3 mg/kg were well tolerated in infants aged <1 year and achieved therapeutic exposure levels. The current study supports the adoption of a universal dosing recommendation for infants. Clinicaltrials.gov unique identifier NCT00988325.